THE FUNCTION OF FUNCTION WORDS IN WILLIAM FAULKNER'S AS I LAY DYING. - Hannon, Charles (Faulkner Journal)
The article offers information on topics related to writer William Faulkner. Topics mentioned include the book "As I Lay Dying," the Linguistic Inquiry and Word Count (LIWC) computer software he developed, and the social aspects of interpersonal relations. Also mentioned are the patterns for men and women language, social aspects of language, and the cognitive processing for language uses.